Biomarkers associated with persistence and severity of IgE-mediated food allergies: a systematic review - Mariana Malucelli; Roque Farias, Junior; Rosiane Guetter Mello; Carolina Prando (Jornal de Pediatria, 2023)
Objective: The prevalence of food allergies (FA) has increased worldwide over the last few decades. Milk, eggs, and peanuts are among the most common allergens and can cause anaphylaxis. Therefore, we aimed to identify biomarkers that could predict the persistence and/or severity of IgE-mediated allergies to milk, eggs, and peanuts via a systematic review. Methods: This systematic review proceeded according to a protocol registered in the International Prospective Register of Systematic Reviews. Two independent authors extracted studies of interest from PubMed, SciELO, EMBASE, Scopus, and Ebsco databases and assessed their quality using the Newcastle-Ottawa Scale. Results: We selected 14 articles describing 1,398 patients. Among eight identified biomarkers, total IgE, specific IgE (sIgE), and IgG4 were the most often cited biomarkers of persistent allergies to milk, eggs, and peanuts. Skin prick tests, endpoint tests, and sIgE cutoff levels may predict positive responses to challenges with these foods. The basophil activation test is a biomarker for the severity and/or threshold of allergic reactions to milk and peanuts. Conclusion: Only a few publications identified possible prognostic indicators of the persistence or severity of FA and outcomes of oral food challenges, indicating that more accessible biomarkers are needed to determine the likelihood of having a severe food allergic reaction.